Influence of tree bunching angles on the productivity and costs of a full tree system - Miyajima, Ricardo Hideaki [UNESP]; de Britto, Pedro Caldas; Tonin, Rodrigo Petrongari [UNESP]; Millani, Thais Maria [UNESP]; Fenner, Paulo Torres [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2019)
The objective of this work was to evaluate the influence of different angulations of the tree bunching on the time, productivity and costs of a full tree harvesting system composed by a feller-buncher and a skidder. The bunches were placed at 45°, 90°, 135° and 180° in relation to the alignment of the forest plantation in which they also represented the necessary angulation for the rotation of the feller-buncher for the formation of the bunches. A work time study was performed in order to obtain the productive time and consequently to estimate productivity and costs of each operation. The feller-buncher's productivity was influenced by the angulations worked and the number of trees per cycle. The feller-buncher presented higher productivities (105.70 m3 h-1) and lower costs (1.80 USD m-3) when operated at 45°. The skidder´s productivity was not influenced by the different angulations of the tree bunching. However it was related with the skidding distance, number of trees per cycle, and speed. The skidder´s productivity was estimated at 181.90 m3 h-1 with a cost of 0.75 USD m-3 when the skidder was operated at 5 km h-1 and 216.50 m3 h-1 with a cost of 0.63 USD m-3 when operated at 7 km h-1
Influência da disposição dos feixes de árvores em diferentes angulações na produtividade e custos de um sistema de árvores inteiras
Keywords: Feller-buncher; Forest harvesting; Skidder; Work time study